PENGARUH MOTIVASI DAN TEORI PEMBELAJARAN HUMANISTIK TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AL-QURAN HADIST - Amir Diki Fauzi Rahman; Dede Aji Mardani (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2025)
One indicator of success in the learning process in schools can be seen from the learning outcomes obtained by students. In learning the Quran Hadith, educators have never implemented active learning strategies so that students feel bored and less enjoyable when learning. This research was conducted in 2 different schools, namely Madrasah Aliyah Nurussalam as an experimental class and Madrasah Aliyah Cidua as a control class. The purpose of this study was to determine the effect of motivation and humanistic learning on student achievement in the subject of Al-Quran Hadith in grade 11. This research approach uses quantitative research methods with field studies. Data collection techniques with formative tests, observation and documentation. The results of the study showed that learning motivation and the application of a humanistic approach significantly have a positive effect on student learning outcomes. Simultaneously, both variables are able to explain about 56.6% of the variation in student learning outcomes, reinforcing the importance of motivation and humanistic learning methods in improving the quality of learning outcomes in the field of religious education, especially the subject of Al-Quran Hadith.